THE IMPLEMENTATION OF E-GOVERNMENT BY MEANS OF THE ONLINE MONITORING APPLICATION FOR STATE TREASURY AND BUDGET (OMSPAN) IN SUMORAME VILLAGE, SIDOARJO REGENCY - Anggraeni, Faradilla Dwi; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Online Monitoring System for State Treasury and Finance (OMSPAN) as an ICT-based innovation in improving village financial management, particularly addressing issues of inefficiency, data inconsistency, and potential misuse in fund disbursement and reporting. Method: A qualitative descriptive approach was employed, utilizing written and oral information obtained through field observations and interviews to provide in-depth insights into the system’s application. Results: Findings indicate that the adoption of OMSPAN in Sumorame Village, Sidoarjo Regency, has enhanced the transparency and efficiency of village fund management sourced from the State Budget (APBN), which has become the main revenue for villages. Supporting factors include increased regulatory support, the availability of financial data, and improved accountability mechanisms, while inhibiting factors involve limited technical capacity and infrastructural challenges. Novelty: This study contributes by highlighting the role of OMSPAN as an e-government innovation at the village level, demonstrating how ICT integration strengthens financial governance in rural contexts, while simultaneously exposing practical challenges that need to be addressed for sustainable implementation.